(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | Among the plotlines in Anna Seghers’ 1959 novel of socialist construction, Die Entscheidung, the love story remains the most realistic allegory for understanding passionate motivations for socialism. This reading reveals how Seghers has moved the locus of insight from characters in her early novels who gain ideological consciousness in mortal struggle against repression to characters who discover ideological limits in the face of creaturely involvements. The sacrifice of the Catholic wife of a communist engineer points to the persistence of the body, labour, and birth, with their concomitant emotions of compassion and romance. By directing attention away from doctrinaire elements, my reading explores how the particulars of care encounter the generalities of collectivism. Résumé | Dans le roman d’Anna Seghers de 1959, Die Entscheidung, roman de construction socialiste, l’histoire d’amour reste l’allégorie la plus réaliste pour comprendre certaines motivations passionnées pour le socialisme. Cette intervention montre comment Seghers a déplacé le lieu de connaissance de la lutte forcenée contre la répression (dans ses premiers romans) aux personnages qui se heurtent aux limites idéologiques devant leurs engagements corporels. Le sacrifice de la femme catholique d’un ingénieur communiste pointe vers la persistance du corps, du travail et de l’accouchement, avec leurs sentiments de compassion et de rêve. En écartant l’attention des éléments doctrinaires, cette intervention interroge les façons dont les particularités des soins rencontrent les généralités du collectivisme.